Causes and Risk Factors for Early Neonatal Mortality in the Western Region of Mongolia - Tsedev, Solongo; Dashnyam, Ulzii; Zagd, Gerelmaa; Badrakh, Burmaajav (Central Asian Journal of Medical Sciences, 2015)
Objectives: The incidence of perinatal, especially early neonatal mortality, has not been reducing in the western region of Mongolia, therefore, the purpose of this study was to identify causes and risk factors for early neonatal mortality in the western region of Mongolia. Methods: A case-control study for neonatal mortality was conducted in 5 hospitals in western Mongolia in 2014. Cases and controls were chosen from the hospitals. Associated causes and risk factors for early neonatal mortality were identified with subgroup binary logistic regression analyses. Results: A total of 7749 live births occurred during the study period. The early neonatal mortality rate was 11.3 per 1000 births. Obstetric complications, obstetric chronic history, abruption of placenta, preeclampsia and maternal diseases influenced early neonatal mortality. Respiratory distress syndrome (OR=29.4; 95% CI, 12.78-67.65, p<0.05), perinatal asphyxia (OR=5.2; 95% CI, 2.81-9.63, p≤0.001), congenital malformation (OR=39.2; 95% CI, 5.11-302.1) and perinatal infections (OR =11.1; 95% CI, 3.64-34.28, p≤0.001) were the leading causes of newborn death in the first week. Conclusion: Overall, high rates of neonatal death demonstrate the need to improve the quality of health care and the control of delivery and factors influencing early neonatal mortality should be studied further at the national level.>